Youth Transition from Education to work in the Mediterranean Region The ETF Experience with Partner Countries [Sample] (2016)
Countries in the Arab Mediterranean region (AMC) face several daunting challenges. changes in the nature work and employment have weakened prospect for secure, long term jobs, just as the 'youth bulge' cause by rapid demographic transition means that almost 30% of the population in these countries is between the ages of 15 and 30. Government have been challenged to respond of these problems. Compiling information from a wide range of sources, this paper assess issues and policy responses necessary to improve school-to-work transitions in AMC countries, analyzing complex inter-relationships among school, work, economic development, and policy. Economic growth, in particular job creation, has not kept pace with educational expansion. At the same time, school graduates frequently lack the skills that employers need. Thus, while more children and youth are completing higher levels of schooling, the education they received is unlikely, for many, to lead to improve well-being. Recommendations are specified around four broad policy areas of improvement, and one of inclusion: 1) improving the level of workforce education and qualifications; 2) improving the content (and evaluating the impact) of government programmes aimed at easing the transition from school to work; 3) improving the framework for transition support, while equipping youth with skills that better match labour market needs; and 4) including youth voices in planning and implementation of the programmes.
Keywords: Educational development